Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) Ta có A = 21 + 22 + 23 + ... + 22022
2A = 22 + 23 + 24 + ... + 22023
2A - A = ( 22 + 23 + 24 + ... + 22023 ) - ( 21 + 22 + 23 + ... + 22022 )
A = 22023 - 2
Lại có B = 5 + 52 + 53 + ... + 52022
5B = 52 + 53 + 54 + ... + 52023
5B - B = ( 52 + 53 + 54 + ... + 52023 ) - ( 5 + 52 + 53 + ... + 52022 )
4B = 52023 - 5
B = \(\dfrac{5^{2023}-5}{4}\)
b) Ta có : A + 2 = 2x
⇒ 22023 - 2 + 2 = 2x
⇒ 22023 = 2x
Vậy x = 2023
Lại có : 4B + 5 = 5x
⇒ 4 . \(\dfrac{5^{2023}-5}{4}\) + 5 = 5x
⇒ 52023 - 5 + 5 = 5x
⇒ 52023 = 5x
Vậy x = 2023
e) \(x+y+3xy=1\)
\(\Leftrightarrow3x+3y+9xy=3\)
\(\Leftrightarrow3x+9xy+3y=3\)
\(\Leftrightarrow3x\left(1+3y\right)+1+3y=4\)
\(\Leftrightarrow\left(3y+1\right)\left(3x+1\right)=4\)
\(\Leftrightarrow\left(3x+1\right);\left(3y+1\right)\in\left\{-1;1;-2;2;-4;4\right\}\)
\(\Leftrightarrow\left(x;y\right)\in\left\{\left(-\dfrac{2}{3};-\dfrac{5}{3}\right);\left(0;1\right);\left(-1;-1\right);\left(\dfrac{1}{3};\dfrac{1}{3}\right);\left(-\dfrac{5}{3};-\dfrac{2}{3}\right);\left(1;0\right)\right\}\)
\(\Leftrightarrow\left(x;y\right)\in\left\{\left(0;1\right);\left(-1;-1\right);\left(1;0\right)\right\}\)
(\(\dfrac{9}{25}\))2 = (\(\dfrac{3^2}{5^2}\)) = (\(\dfrac{3}{5}\))4 \(\ne\) ( \(\dfrac{3}{5}\))-4
a) \(\dfrac{a}{b}=\dfrac{c}{d}=\dfrac{a+c}{b+d}\)
\(\Rightarrow\left(b+d\right)c=\left(a+c\right)d\)
\(\Rightarrow dpcm\)
b) \(\dfrac{a}{b}=\dfrac{c}{d}=\dfrac{2a}{2b}=\dfrac{c}{d}=\dfrac{2a+c}{2b+d}=\dfrac{2a-c}{2b-d}\)
\(\Rightarrow\left(2b-d\right)\left(2a+c\right)=\left(2a-c\right)\left(2b+d\right)\)
\(\Rightarrow dpcm\)
c) \(\dfrac{a}{b}=\dfrac{c}{d}=\dfrac{3c}{3d}=\dfrac{3a}{3b}=\dfrac{5c}{5d}=\dfrac{3a+5c}{3b+5d}=\dfrac{a-3c}{b-3d}\)
\(\Rightarrow\left(b-3d\right)\left(b-3d\right)=\left(3b+5d\right)\left(a-3c\right)\)
\(\Rightarrow dpcm\)
Đính chính câu c
\(\Rightarrow\left(3a+5c\right)\left(b-3d\right)=\left(3b+5d\right)\left(a-3c\right)\)
\(2\dfrac{3}{x}\) là hỗn số hay là \(2\times\dfrac{3}{x}\) vậy bạn .
\(\dfrac{7}{11}\) - \(\dfrac{4}{29}\) + \(\dfrac{1}{37}\) - \(\dfrac{1}{37}\) + \(\dfrac{4}{29}\) - \(\dfrac{1}{2}\)
= ( \(\dfrac{7}{11}\) - \(\dfrac{1}{2}\)) - ( \(\dfrac{4}{29}\) - \(\dfrac{4}{29}\)) + ( \(\dfrac{1}{37}\) - \(\dfrac{1}{37}\))
= \(\dfrac{14}{22}\) - \(\dfrac{11}{22}\) - 0 + 0
= \(\dfrac{3}{22}\)